Evaluation of different treatment modalities for fractured and non-fractured simple bone cyst: A single-center review of 68 patients. Issue 31 (6th August 2021) - Deventer, Niklas; Deventer, Nils; Gosheger, Georg; de Vaal, Marieke; Budny, Tymoteusz; Luebben, Timo; Frommer, Adrien; Vogt, Bjoern
Abstract : Abstract: Simple bone cysts (SBCs) occur most frequently in the proximal aspect of the humerus and femur in growing age and are associated with intercurrent pathological fractures in up to 87%. Therapeutic management of SBCs remains controversial. The aim of this study was to examine the outcome of conservative and various surgical treatment modalities considering the specific anatomic location and integrity of the SBC. In this retrospective study, we analyzed 68 cases of SBCs who underwent a conservative or surgical treatment between 2009 and 2020 with a mean follow-up of 30.1 months. The epidemiological characteristics, complications, clinical, and radiographic outcome after conservative or surgical treatment were assessed. The study includes 50 male (73.5%) and 18 female (26.5%) patients with a mean age of 9.1 years. The most common locations were the proximal humerus (69.2%, n = 47) and femur (16.2%, n = 11). In 43 cases (63.2%; upper limb n = 40, lower limb n = 3) a pathological fracture occurred. Fifty patients (73.5%; upper limb n = 40, lower limb n = 10) underwent a conservative treatment. In 11 cases (16.2.1%; upper limb n = 4, lower limb n = 7) an intralesional curettage and defect reconstruction with bone substitute without stabilization were performed. Five patients (7.3%; upper limb n = 4, lower limb n = 1) received an osteosynthesis, in two cases (2.9%; upper limb 1; lower limb 1) combined with an intralesional curettage and defect reconstruction with bone substitute. All 32 pathological fractures treated conservatively (upper limb n = 31, lower limb n = 1) healed within 6 weeks; 17/43 patients (39.5%) suffered at least one second fracture. After intralesional curettage and defect reconstruction with bone substitute local recurrence was observed in 5/13 cases (38.5%). Spontaneous consolidation, at least partially, was observed in three cases (4.4%) following conservative treatment after fracture. No relevant secondary angular or torsional deformity was observed after treatment. The majority of SBCs can be treated conservatively, especially in the upper extremity. However, if a fracture is completely dislocated, joint affecting, unstable or open, surgical treatment is necessary. Load-dependent pain or the inability to mobilize timely after fracture can necessitate surgical treatment in SBCs affecting the lower extremity. Spontaneous resolution, especially after fracture, can be seen in rare cases.